Analysis of Operation Effectiveness Evaluation Technique of Power Trading Center Based on Coefficient of Variation Method-TOPSIS Modeling - He, Letian; Sun, Lili; Lin, Ye; Weng, Jiayan (2025 4th International Conference on Smart Grid and Green Energy (ICSGGE), 2025)
With the deepening of China's electricity market-oriented reform, the current power market is characterized by large-scale, multi-cycle, multi-subject, and low-carbon power supply, and the power trading center is facing new challenges. In this context, it is very important to improve the operation and management level of the power trading center for the sustainable operation and development of enterprises. Therefore, this paper proposes an evaluation technology for the operation effect of the power trading center based on the coefficient of variation method-TOPSIS model based on the actual operation and management of the power trading center, so as to provide reference and reference for enterprises to reasonably carry out the evaluation of the operation effect and improve the efficiency and effectiveness of operation and management.